Szycher's handbook of polyurethanes - Szycher, M. (CRC Press, 2013)
"Written as a reference for polyurethane technologists and end users, raw materials suppliers, and students in the field, this second edition covers the technical advances in the field over the past 10 years. Filled with tables, charts, and photographs, it includes new data on green polyurethanes, automotive applications, new coatings, new manufacturing equipment, new health-care uses, and other topics. Individuals from all major polyurethane intermediate suppliers and equipment manufacturers contributed to this updated handbook, and discuss current products and provide a comprehensive list of product portfolios"--Provided by publisher